In Lessing’s Footsteps: Dramaturgy in Germany and Britain - Michael Raab (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2021)
The first part of the essay outlines the history of dramaturgy in Germany and Britain, the second part deals with the different new writing policies there.